Reproducing the national family: kinship claims, development discourse and migrant caregivers in Palestine/Israel. (August 2019) - Brown, Rachel H.
This article probes the politics of the migrant caregiver/citizen-employer relationship in Palestine/Israel as it unfolds within the Jewish-Israeli home. Based on interviews with migrants from the Philippines, Nepal, India and Sri Lanka and their Jewish-Israeli employers, I examine how Israel's ethno-racially hierarchical citizenship regime and the transnational gendering and racialisation of carework manifest in this relationship. I begin by situating migrant women working as caregivers within the legal and political context of Palestine/Israel, delineating how gendered constructions of the Jewish-Israeli woman uphold the borders of the nation and paint non-Jewish migrant women as reproductively threatening. I then analyse two common tropes among citizen-employers in describing migrant caregivers. The first, what I term the 'kinship trope', characterizes them as 'one of the family', obscuring the ethno-racial basis of the state. I show how this trope contrasts sharply with Zionist settler colonial rhetoric portraying Jewish-Israelis as 'one big family'. The second trope represents migrant women as individual agents of economic development and Israel as a market-driven, neoliberal society that is equally a state for all its citizens. By depicting Israel as a 'modern', 'progressive' state that is an exemplar of gender equality, this trope again masks the ethno-racial basis of citizenship, as well as gender disparities. Finally, I argue for a feminist approach to migrant carework that accounts for the ways neoliberal labour formations are mediated by gendered racisms specific to a particular state's racial nation-building project.